Gamification as a Strategy for Increasing Learning Engagement: A Bibliometric Analysis and Implications for Online Learning - Rosyidah, Salsabila Dwi; Pamungkas, Heni Purwa; Dewi, Retno Mustika (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This research is motivated by the research and implementation of online learning since the COVID-19 pandemic, which has raised issues of declining student motivation and participation, necessitating innovative strategies such as gamification to increase learning engagement in digital environments. This study aims to map research trends, key themes, and collaborations in gamification research during the 2015–2025 period. The approach used includes descriptive analysis and scientific network analysis through co-authorship, co-occurrence, and co-itation. The research subjects consisted of 478 Scopus-indexed articles analyzed using Bibliometrix software with the Biblioshiny tool. The results show that the number of publications on gamification has increased significantly with an annual growth rate of 27.38% supported by high citations per document, indicating the high relevance and scientific contribution of this topic. Key themes such as digital education, psychology and motivation, technology, and marketing are central themes with strengthening research in the field of education. The research network is dominated by collaborations in Europe, America, and Australia. The novelty of this research lies in its comprehensive analysis, which not only maps publication trends but also links them to gamification strategies for motivation and participation in the context of bold learning. The implications of this research encourage the use of gamification in the digital-era learning transformation of Merdeka Belajar (Freedom to Learn), combining Virtual Reality (VR) environments with gamification elements and incorporating digital literacy, creativity, problem-solving, and collaboration.